Adult Laryngeal Hemangioma – A Rare Case Report - Chen, IHK; Abdul Jalal, SY; B, Singh; Mat Baki , M (IIUM Medical Journal Malaysia, 2020)
Laryngeal hemangiomas are classified into an adult and infantile forms. The incidence of laryngeal hemangioma in adults is rare. While infantile hemangiomas are more frequently found in subglottic regions and regress with age, adult hemangiomas occur commonly in supraglottic and glottic regions and they do not regress spontaneously. In this article, we report a case of laryngeal cavernous hemangioma in a 51-year-old male who was treated successfully with endolaryngeal microsurgical technique without any recurrence through one year follow up.